Molecular aspects of oxidative drug metabolizing enzymes : their significance in environmental toxicology, chemical carcinogenesis and health - Arinc, Emel; Schenkman, John B; Hodgson, Ernest (Springer, 1995)
Presented here are recent advances in biochemical, toxicological, and regulatory aspects of oxidative drug metabolizing enzymes. Mainly cytochrome P450-dependent and flavin-containing monooxygenases (FMO) are covered. Moreover, the book deals with genotoxicity studies and toxicological interactions of environmental chemicals and mechanisms of mutagenicity and tumor formation. The construction of genetically engineered mammalian cells for the production of a specific P450 isozyme and the application of these cell lines in drug metabolism, mutagenicity and toxicity studies are described in detail. Further, insight is provided into how a number of aquatic species cope with pollutants and their genotoxicity.
NATO Advanced Study Institutes ; Cell biology Vol. 90
Keywords: Xenobiotics; Carcinogenicity Tests; toxikologie; systém (enzymů) cytochromů P-450; Cytochrome P-450 Enzyme System; testy karcinogenity; xenobiotika